2023
DOI: 10.1080/02670836.2023.2180902
|View full text |Cite
|
Sign up to set email alerts
|

Alloying, phases and magnetic behaviour of mechanically alloyed FeNiMnCu-based high entropy alloys

Abstract: In the present work, FeNiMnCuX (X: Co, Cr, Mo, Ti, W) high entropy alloys are successfully fabricated by mechanical alloying. After 15 h of milling, FeNiMnCu and FeNiMnCuCo alloys form a single FCC structure, while other alloys formed an FCC + BCC mixture structure. All alloys contained homogeneous distributions of Fe and Ni, while Cu was segregated. Alloys FeNiMnCuTi and FeNiMnCuW exhibited homogeneous distributions of Mn, whereas others exhibited Mn-rich islands. Except for the FeNiMnCuTi alloy, all alloys e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Table 3 provides a comprehensive overview of stability criteria (Ω, Λ, ϕ Ye , and ) for the two studied alloys and a wide range of other alloys produced via mechanical alloying, drawn from various sources in the literature [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. The table shows the reported microstructure in the as-milled state as well as in the annealed state.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 provides a comprehensive overview of stability criteria (Ω, Λ, ϕ Ye , and ) for the two studied alloys and a wide range of other alloys produced via mechanical alloying, drawn from various sources in the literature [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. The table shows the reported microstructure in the as-milled state as well as in the annealed state.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, the low hardness, strength and wear resistance greatly limit their applications and the high CTE of Cu seems to be incompatible with chip materials. [8][9][10] In this context, the excellent mechanical properties and low CTE of highentropy alloys (HEA) at room temperature offer the opportunity to broaden the choice of substrates. [11][12][13][14] For example, Lin et al 15 found that CoCrFeNiTiNbBx HEA coating can significantly improve the wear resistance of the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, mechanical alloying (MA), as a solid-state coating deposition process, has shown great potential in the preparation of nanomaterials, thermoelectric materials, superconducting materials and other new materials. 10 Compared to other coating deposition techniques, MA can avoid defects caused by metallurgical reactions. 20 At the same time, metal matrix composite (MMC) coatings have received much attention as a ductile-brittle system, in which some ductile materials (such as Fe, 21 Cu, 22 et al) are used as binders and various reinforcement phases such as HEAs, 23 TiC, 24 WC 25 and TiO 2 2 are added to obtain excellent mechanical or thermal properties.…”
Section: Introductionmentioning
confidence: 99%